1997
DOI: 10.1002/(sici)1097-4652(199702)170:2<106::aid-jcp2>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Intimal hyperplasia following vascular injury is not inhibited by an antisense thrombin receptor oligodeoxynucleotide

Abstract: Thrombin is a multifunctional serine protease with central functions in hemostasis, but demonstration of its role in the initiation and maintenance of cell proliferation which occurs following vascular injury is still lacking. To determine the role played by thrombin and its receptor in neointimal accumulation of smooth muscle cells in a rabbit carotid artery model, we have used an 18 mer antisense phosphorothioate oligonucleotide (ODN) directed against the translation initiation region of the human thrombin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…These data suggest that EPR-1/factor Xa plays a direct role in restenosis in this animal species. This study complements our previous work in the same animal model using the specific thrombin inhibitor recombinant desulphatohirudin (35), and lends support to the hypothesis that elements of the coagulation system, either through thrombus formation or because of other mitogenic effects, are important in restenosis after vascular injury in this animal model. Therefore, our results demonstrate the existence of functional factor Xa receptors on SMCs, related to EPR-1, represent the first evidence for the possible importance of EPR-1 in the mitogenic effect of factor Xa for these cells, and raise the interesting possibility of an active role of this factor Xa receptor in several processes where abnormal SMC proliferation has been acknowledged, such as atherogenesis.…”
Section: Discussionsupporting
confidence: 86%
“…These data suggest that EPR-1/factor Xa plays a direct role in restenosis in this animal species. This study complements our previous work in the same animal model using the specific thrombin inhibitor recombinant desulphatohirudin (35), and lends support to the hypothesis that elements of the coagulation system, either through thrombus formation or because of other mitogenic effects, are important in restenosis after vascular injury in this animal model. Therefore, our results demonstrate the existence of functional factor Xa receptors on SMCs, related to EPR-1, represent the first evidence for the possible importance of EPR-1 in the mitogenic effect of factor Xa for these cells, and raise the interesting possibility of an active role of this factor Xa receptor in several processes where abnormal SMC proliferation has been acknowledged, such as atherogenesis.…”
Section: Discussionsupporting
confidence: 86%
“…[35][36][37] The antisense thrombin receptor oligodeoxynucleotide did not inhibit intimal hyperplasia after vascular injury. 38 This study showed that rTM significantly inhibited SMC DNA synthesis and proliferative effect induced by thrombin. Thrombomodulin is constitutively produced on the endothelium and functions as a key factor in maintaining the nonthrombogenic vessel surface.…”
Section: Discussionmentioning
confidence: 80%
“…Thrombin inhibitors [34][35][36][37] and antisense thrombin receptor oligodeoxynucleotide 38 have been studied for the prevention of SMC proliferation. This study demonstrated that hirudin, a direct thrombin inhibitor, inhibited SMC proliferation induced by thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…Although heparin is a potent inhibitor of SMC growth and intimal hyperplasia in some animal models, it has been ineffective in inhibiting restenosis in studies both animal 44 and human. Other studies have demonstrated varying results with use of hirudin [45][46][47][48][49][50] and argatroban [51][52][53] with respect to their effects on SMC physiology and inflammation in vitro or in the setting of arterial injury. Most show some promise, but are limited solely to the effects resulting from thrombin inhibition.…”
Section: Discussionmentioning
confidence: 99%